Estudo da temperatura de globo em relação à temperatura do ar durante atividades cognitivas em ambientes de ensino com alterações climáticas em áreas das regiões brasileiras - Brito, Flávia Brandão Ramalho de (2017)
Introduction: The planet's climate change may raise the average temperature in all regions of Brazil. As there has been an increase in the insertion of technological innovations of communication and information (news ICT) in educational institutions, which can contribute to the increase in thermal radiation, it is therefore important to investigate how this increase in these environments may interfere with the comfort and performance of students. In the equation formulated by Fanger (1970), the thermal radiation factor is represented by the mean radiant temperature (Trm), but its impact on thermal comfort is often ignored. The globe temperature (Tg) is one of the variables of the equations for the calculation of the mean radiant temperature. It corresponds to the temperature that allows evaluating the level of thermal radiation of the existing surfaces in an environment where a significant difference between the globe temperature and the temperature of the air can demonstrate some increase of thermal radiation in the work environment. Objective: To investigate if the behavior of the globe temperature in relation to the air temperature (Tg-Ta), observing the variation of the mean radiant temperature, could have repercussion in the performance of students in intelligent teaching environments in areas of the Brazil's regions. Methods: The methodological procedures adopted in this work consisted of the following steps: analysis of thermal variables: Trm and (Tg-Ta); analysis of students' performance, analysis of architectural elements and construction of the mathematical model. The study was carried out in computerized laboratories with News ICT in the following institutions: UFPI, Teresina-Piauí (A); UFSC, Florianópolis-Santa Catarina (B); UnB, Brasília-Federal District (C); UNIVASF, Petrolina-Pernambuco (D); ICMC, São Carlos-SP (E); UFAM, Manaus-Amazonas (F); CE of the PM, João Pessoa, Paraíba (G). The students answered a questionnaire adapted from the Bateria de Provas de Raciocínio (BPR-5) on three consecutive days at different temperatures, while the thermal conditions were measured and the design and architectural elements were analyzed. Results: It was verified that in the three consecutive days, there was no heat exchange by radiation between the student and his environment in the laboratories of institutions C and F, demonstrating that in the other laboratories of institutions A, B, E and G there was heat exchange by radiation. It is noteworthy that in the laboratory of institution G this heat exchange was more pronounced, such that the mean radiant temperature at any given time exceeded the globe temperature at 2.25°Chcg/ . However, their architectural analysis signaled that the design was adequate. So probably, the heat sources inside the laboratory should have provided increased thermal radiation, given that the number of students and laptops were representative. Thus, in the sense of confirming these findings, it was verified through the mathematical modeling that with each increase of one degree in the difference between the globe temperature and the air temperature (Tg-Ta), the students' performance in the computer laboratory of the Institution G decreased by around 29%. Therefore, the higher the mean radiant temperature, the higher the thermal radiation in this laboratory, and this increase may compromise student performance. Conclusion: Productivity may change due to changes in air temperature in air-conditioned teaching environments, as has already been demonstrated by international publications. In this specific case, if Tg >> Ta, the thermal radiation may possibly interfere with the performance of people present in environments equipped with technological innovations in communication and information (News ICT).